ResolvinD1 Protects the Airway Barrier Against Injury Induced by Influenza A Virus Through the Nrf2 Pathway - Guo, Yan; Tu, You-Hui; Wu, Xu; Ji, Shuang; Shen, Ji-Long; Wu, Hui-Mei; Fei, Guang-He (Frontiers in Cellular and Infection Microbiology, 2021)
Airway barrier damage and excessive inflammation induced by influenza A virus (IAV) are associated with disease progression and prognosis. ResolvinD1 (RvD1) is a promising lipid mediator with critical protection against infection in the lung. However, whether RvD1 protects against IAV-induced injury and the underlying mechanisms remain elusive. In this study, primary normal human bronchial epithelial (pNHBE) cells were isolated and co-cultured with IAV and/or RvD1. Then, the expressions of E-cadherin, Zonula occludins-1, inflammatory mediators and proteins in Nrf2-dependent pathway were detected. To further explore the mechanisms, Nrf2 short hairpin RNA (Nrf2 shRNA) was applied in pNHBE cells. Furthermore, mice were infected with IAV, and were subsequently treated with RvD1. We found that IAV downregulated expressions of E-cadherin, Zonula occludins-1, Nrf2 and HO-1, upregulated the phosphorylation of NF κ B p65 and IKBα, levels of IL-8 and TNF-α, as well as ROS production. RvD1 reversed these damaging effects induced by IAV. However, when Nrf2 expression was suppressed with shRNA in pNHBE cells, the protective effects of RvD1 on IAV-induced injury were inhibited. In vivo studies further demonstrated that RvD1 could alleviate barrier protein breakdown and reduce airway inflammatory reactions. Collectively, the study demonstrated that RvD1 could play dual beneficial roles in protecting airway epithelium barrier function and reducing inflammation via the Nrf2 pathway, which may provide a better treatment option for influenza A virus infection.